A Rare Case of Cavitary Lesion of the Lung Caused by Mycoplasma pneumoniae in an Immunocompetent Patient. (21st August 2017) - Kashif, Muhammad; Dudekula, Rizwan Ahmed; Khaja, Misbahuddin
Abstract : Mycoplasma pneumoniae is an atypical bacterium that most commonly causes upper respiratory tract infections, but it can also cause pneumonia, referred to as "walking pneumonia." Although cavitary lesions are present in a wide variety of infectious and noninfectious processes, those attributable to M . pneumoniae are extremely uncommon; thus, to date, epidemiological studies are lacking. Here, we present a rare case of a 20-year-old male, referred to us from a psychiatric facility for evaluation of a cough, who was found to have a cavitary lesion in the right upper lobe. An extensive workup for cavitary lesion was negative, but his mycoplasma IgM level was high. A computed tomography (CT) of the chest confirmed the presence of a cavitary lesion. After treatment with levofloxacin antibiotics, a follow-up CT showed complete resolution of the lesion. Our case is a rare presentation of mycoplasma pneumonia as a cavitary lesion in a patient without any known risk factors predisposing to mycoplasma infection. Early recognition and treatment with an appropriate antibiotic may lead to complete resolution of the cavitary lesion.